2008
DOI: 10.1371/journal.pone.0003318
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Deficiency Affects the Formation of Chromosomal Translocations by Homologous Recombination in Saccharomyces cerevisiae

Abstract: Telomerase is a ribonucleoprotein complex required for the replication and protection of telomeric DNA in eukaryotes. Cells lacking telomerase undergo a progressive loss of telomeric DNA that results in loss of viability and a concomitant increase in genome instability. We have used budding yeast to investigate the relationship between telomerase deficiency and the generation of chromosomal translocations, a common characteristic of cancer cells. Telomerase deficiency increased the rate of formation of spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 77 publications
4
20
0
Order By: Relevance
“…Identification of the reciprocal translocation (see Fig. 1A) occurred only in a small subset of His + recombinants (1/14), which is similar to previous reports (55,56) (Table S2). To ascertain whether our assay fulfills the criteria that define MMEJ, we examined the effect of ku70Δ, lig4Δ, and rad52Δ single mutants on the frequency of MMEJ repair.…”
Section: Development Of An Interchromosomal Mmej Assay With Varying Mhsupporting
confidence: 89%
See 1 more Smart Citation
“…Identification of the reciprocal translocation (see Fig. 1A) occurred only in a small subset of His + recombinants (1/14), which is similar to previous reports (55,56) (Table S2). To ascertain whether our assay fulfills the criteria that define MMEJ, we examined the effect of ku70Δ, lig4Δ, and rad52Δ single mutants on the frequency of MMEJ repair.…”
Section: Development Of An Interchromosomal Mmej Assay With Varying Mhsupporting
confidence: 89%
“…Newly dissected mutant spores of rad52::TRP1, pol4::KANMX rad52:: TRP1 pol3-ct rad52::TRP1, and rad1::LEU2 rad52::TRP1 double mutants possessing the interchromosomal MMEJ substrates, which share 14-2-4 bp of MH, were grown in YPD overnight, diluted to an OD 600 of 0.2 in fresh YP-Raffinose, and allowed to grow to an OD 600 of ∼1.0, at which time 45 mL was removed (0 h), pelleted, and immediately subject to the ChIP procedure described previously (56). Galactose was added to the remaining culture to a final concentration of 2% (vol/vol), which induces the expression of HO endonuclease and DSB formation at the his3Δ3′ allele.…”
Section: Methodsmentioning
confidence: 99%
“…1; Meyer and Bailis 2008; Pannunzio et al 2008). DSBs are initiated adjacent to each of the truncated alleles that share either 60 or 311 bp of sequence homology, so as to mimic the approximate size of common repetitive elements.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that simultaneous HO endonuclease-catalyzed DSBs adjacent to appropriately oriented 60 or 300 bp repetitive sequences on different chromosomes in wild-type diploid cells results in the appearance of chromosomal translocations in 1 to 10% of the survivors (Figure 1, Table 1) [38], [39]. This process, referred to as T2, utilizes two truncated copies of the HIS3 gene that share 60 or 300 bp homologous segments [38].…”
Section: Resultsmentioning
confidence: 99%